2005
DOI: 10.1242/jcs.01693
|View full text |Cite
|
Sign up to set email alerts
|

Inositol (1,4,5)-trisphosphate receptor links to filamentous actin are important for generating local Ca2+ signals in pancreatic acinar cells

Abstract: We explored a potential structural and functional link between filamentous actin (F-actin) and inositol (1,4,5)-trisphosphate receptors (IP3Rs) in mouse pancreatic acinar cells. Using immunocytochemistry, F-actin and type 2 and 3 IP3Rs (IP3R2 and IP3R3) were identified in a cellular compartment immediately beneath the apical plasma membrane. In an effort to demonstrate that IP3R distribution is dependent on an intact F-actin network in the apical subplasmalemmal region, cells were treated with the actin-depoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…In related Apicomplexans equivalent structures are also connected by short F-actin strands (Jewett and Sibley, 2003). A similar structure/function effect is discussed for mammalian cells whose cortical Ca 2+ stores may be positioned by F-actin (Rosado and Sage, 2000;Wang et al, 2002;Roderick and Bootman, 2003;Turvey et al, 2005). Although we could not show such an effect in response to cytochalasin in Paramecium (Mohamed et al, 2003), this may be due to the involvement of drug-insensitive isoforms.…”
Section: Nuclear and Cell Divisionmentioning
confidence: 55%
“…In related Apicomplexans equivalent structures are also connected by short F-actin strands (Jewett and Sibley, 2003). A similar structure/function effect is discussed for mammalian cells whose cortical Ca 2+ stores may be positioned by F-actin (Rosado and Sage, 2000;Wang et al, 2002;Roderick and Bootman, 2003;Turvey et al, 2005). Although we could not show such an effect in response to cytochalasin in Paramecium (Mohamed et al, 2003), this may be due to the involvement of drug-insensitive isoforms.…”
Section: Nuclear and Cell Divisionmentioning
confidence: 55%
“…In neurons, a protein 4.1N-InsP 3 R complex may be associated with cytoskeletal elements enriched in postsynaptic compartments (301). It has been widely observed that disruption of the actin filament network has profound effects on InsP 3 -evoked Ca 2ϩ signals (56,387,484,503). Actin plays a role in the translational mobility of InsP 3 R-1 (148) but not InsP 3 R-3 (132, 148).…”
Section: Adapter Proteins (Protein 41n Ankyrin and Homer)mentioning
confidence: 99%
“…3206 Journal of Cell Science 123 (18) It is well established that InsP 3 Rs are enriched beneath the apical plasma membrane of polarized epithelia (Lee et al, 1997;Nathanson et al, 1994;Yule et al, 1997); as shown by immunohistochemistry, the receptors colocalize with apical markers such as the F-actin apical web (Waterman-Storer and Salmon, 1998), and tight-junction markers such as ZO-1 (Larina et al, 2007;Turvey et al, 2005). The mechanisms of this localization are not well understood but disruptions of both the microtubular system (Colosetti et al, 2003) and the F-actin network perturb the generation of Ca 2+ signals (Turvey et al, 2005).…”
Section: Mechanisms Of Regional Targeting Of the Camentioning
confidence: 99%
“…The mechanisms of this localization are not well understood but disruptions of both the microtubular system (Colosetti et al, 2003) and the F-actin network perturb the generation of Ca 2+ signals (Turvey et al, 2005). It has been proposed that the microtubular system acts to position the ER (Fogarty et al, 2000c) and that F-actin is part of a complex that specifically anchors InsP 3 Rs (Foskett et al, 2007).…”
Section: Mechanisms Of Regional Targeting Of the Camentioning
confidence: 99%